The Regulation of the American Territories in the Cádiz Constitution of 1812 - Núñez Martínez, María Acracia (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2015)
This essay sets out to underline how important the process of convening at Cortes (parliament) was to the creole elite, and likewise the parliamentary work of the American representatives, as reflected in their speeches and the various Memoranda, which had already been discussed in their places of origin before being presented to the Constituent Parliament.